Isolation and preliminary screening of lactic acid bacteria for antimicrobial potential from raw milk - El Ahmadi, Kawthar; Haboubi, Khadija; El Allaoui, Hasnae; El Hammoudani, Yahya; Bouhrim, Mohamed; Eto, Bruno; Shahat, Abdelaaty A.; Herqash, Rashed N. (Frontiers in Microbiology, 2025)
Lactic acid bacteria (LAB) are widely recognized for their role in food preservation and their potential to produce bacteriocins, natural antimicrobial peptides effective against a broad spectrum of foodborne pathogens. This study focuses on the isolation and characterization of bacteriocin-producing LAB strains from raw milk samples collected in southern and Northern Morocco. Phenotypic and genotypic methods were used to identify the isolated strains, and their antimicrobial activity was evaluated against common foodborne pathogens, including Escherichia coli and Salmonella spp. The results revealed several LAB strains with significant bacteriocin production and strong inhibitory effects against the target pathogens. These findings highlight the potential applications of these strains in the food industry, particularly for enhancing the safety and shelf life of fermented food products. This study provides a foundation for future research on the biotechnological exploitation of LAB as natural food preservatives.